2019
DOI: 10.3390/ijerph16091515
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Immunity for Hepatitis B Virus among Heathcare Workers and Italian Medical Students 20 Years after Vaccination

Abstract: Background: Immunization of healthcare workers (HCWs) and medical students for the hepatitis B virus (HBV) is a crucial part of the hospital infection control programs. The aim of our study was to evaluate the persistence of anti-HBV specific antibodies in HCWs vaccinated during infancy or adolescence. Methods: Medical records of 734 consecutive subjects born after 1980 (481 females, 65.5% and 253 males, 34.5%) who underwent serological testing for anti-hepatitis B surface antibodies (anti-HBs) were evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
5
18
2
8
Order By: Relevance
“…Furthermore, in our study, the percentage of students with titers <10 mIU/mL was relatively higher than that found in other studies that evaluated medical students in Italy (40.8%, 29.3%, 12%, 15.8%) and lower with respect to that in other countries (72.4% in Malaysia, 59% in Israel) [22][23][24][25][26].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, in our study, the percentage of students with titers <10 mIU/mL was relatively higher than that found in other studies that evaluated medical students in Italy (40.8%, 29.3%, 12%, 15.8%) and lower with respect to that in other countries (72.4% in Malaysia, 59% in Israel) [22][23][24][25][26].…”
Section: Discussioncontrasting
confidence: 87%
“…For this reason and consistent with the Centers for Disease Control and Prevention (CDC) recommendations, anti-HBs testing was performed for all students upon admission to medical school if a recent protective titer was not available. All students with anti-HBs titers <10 mIU/mL were thus administered a booster dose, and the large majority responded to the vaccination with a considerable increase in the anti-HBs titer after 1 month, as reported in nearly all other studies [24,36,37].…”
Section: Discussionmentioning
confidence: 71%
“…The decrease in anti-HBs antibodies over time below the seroprotection threshold is a controversial issue. Several studies have shown that individuals with aHBs levels between 1 and 9.99 mIU/mL quickly recover seroprotective aHBs levels after receiving a booster [19][20][21][22], due to immune memory [23,24]. In this context, the available bibliography widely reports that individuals with aHBs levels between 1 and 9.99 mIU/mL mostly generate an adequate anamnestic response and, therefore, are considered protected against HBV infection [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Occupational Physicians should consider with particular attention the evaluation of the persistence of anti-HBV specific antibodies in medical students (in most cases vaccinated at birth age) and HCWs specifically at the time of the first employment in order to identify subjects with non-protective anti-HBs titer [32, 33]. Occupational Physicians’ contribution to reduce vaccine delays or refusals and vaccine hesitancy that are also affecting HCWs is crucial [34].…”
Section: Discussionmentioning
confidence: 99%